The Relationship Between Histopathological Grading and Metastasis in Colorectal Carcinoma Patients - Rahmawati Minhajat; Andi Fachruddin Benyamin; Upik Andariana Miskad (Faculty of Medicine, Hasanuddin University., 2020)
Introduction: To Colorectal cancer (CRC) is a malignancy in the large intestine caused by uncontrolled cell growth. The cause of death due to metastasis and the prognosis is determined by the stage that can be assessed using Dukes classification or TNM (Tumor Nodes Metastasis) staging system. Determination of histopathological grading is important because of the differences in radiosensitivity, local behaviour and the metastasis tendency. The aim of this study is to determine the relationship between histopathological grading and metastasis in colorectal cancer patients. Methods: This study is a cross-sectional study using secondary data from the medical records of CRC patients at the RS. Dr. Wahidin Sudirohusodo and its networking hospital, that were obtained by consecutive sampling. Inclusion criteria are all patients who had surgery and have the results of histopathology, radiology and other datas that may be used as a reference for determining the staging based on the Dukes classification and TNM staging system Results: The number of CRC patients during January 2008 to April 2012 was 268 patients, 55,6% of them were males and mostly their age were around 51-60 years old (25,4%). Most of the CRC location was in the rectum (61,2%) and the highest number of metastasis location was in lymph nodes (40,4%). Out of 179 patients who had result of histopathological examination, adenocarcinoma type (100%) and moderately differentiated adenocarcinoma (45,3%) were the most frequently histopathological grading found. Most of the CRC stage based on the TNM staging system was stage IV (27,4%) and based on the Dukes classification was stage D (26,8%). There is a significant relationship (p<0,001) between histopathological grading and metastasis, and it showed that poorly differentiated adenocarcinoma was more frequent in advanced stage, based on both the Dukes classification and TNM staging system. Conclusions: There is a significant relationship between histophological grading and metastasis. Poorly differentiated adenocarcinoma is more likely to be found in advanced stage of CRC.